The Influence of Discipline and Work Motivation on the Performance of Educational Personnel with Organizational Commitment as an Intervening Variable - Yolanda KUMALASARI; Ernani HADIYATI; Tri Cicik WIJAYANTI (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the influence of work discipline and work motivation on the performance of educational staff, with organizational commitment as a mediating variable, in educational staff at the Faculty of Law, Brawijaya University, Malang. The approach used is quantitative with a survey and explanatory design. The entire population consisting of 46 people were used as respondents through a census technique. Primary data were collected using a Likert-scale-based questionnaire and analyzed using path analysis using SPSS version 26. The results show that work discipline and work motivation have a positive and significant effect on performance, both directly and indirectly through organizational commitment as a mediating variable. This means that increasing work discipline and motivation not only has a direct impact on improving performance but can also strengthen performance through increasing organizational commitment. These findings emphasize the importance of building a work culture that supports discipline and motivation, as well as strengthening organizational commitment as a foundation for improving educational staff performance. Therefore, policies and leadership are needed that are able to encourage the development of these three aspects in an integrated manner to achieve sustainable work effectiveness in the higher education environment.